2019
DOI: 10.1158/1538-7445.am2019-1016
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1016: The androgen receptor splice variant AR-V7 associates with the glucocorticoid receptor following androgen blockade

Abstract: Expression of the constitutively active androgen receptor splice variant AR-V7 is associated with resistance to anti-androgen therapies and worse clinical outcomes in prostate cancer. Dimerization is a requirement for AR-V7 transcriptional activity, but whether that occurs through homodimerization or heterodimerization remains poorly understood. Because NR3C-family nuclear hormone receptors rely on a highly conserved D-box motif within the DNA-binding domain to mediate dimerization, we hypothesized that AR-V7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although evidence to support a direct relationship between AR-V7 and GR is limited, AR-V7 interacts with ligand-bound members of the NR3C-family of nuclear hormone receptors, including full-length AR and GR. One study showed AR-V7 and GR could occupy the same genomic sites in a ligand-dependent manner, suggesting that AR-V7 can utilize GR as an alternative binding partner to initiate heterodimerization transcriptional activation (30).…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence to support a direct relationship between AR-V7 and GR is limited, AR-V7 interacts with ligand-bound members of the NR3C-family of nuclear hormone receptors, including full-length AR and GR. One study showed AR-V7 and GR could occupy the same genomic sites in a ligand-dependent manner, suggesting that AR-V7 can utilize GR as an alternative binding partner to initiate heterodimerization transcriptional activation (30).…”
Section: Discussionmentioning
confidence: 99%